Feedback Seeking in Early Adolescence: Self-Enhancement or Self-Verification?. (April 2013) - Rosen, Lisa H.; Principe, Connor P.; Langlois, Judith H.
The authors examined whether early adolescents ( N = 90) solicit self-enhancing feedback (i.e., positive feedback) or self-verifying feedback (i.e., feedback congruent with self-views, even when these views are negative). Sixth, seventh, and eighth graders first completed a self-perception measure and then selected whether to receive positive or negative feedback from an unknown peer in different domains of self. Results were consistent with self-verification theory; adolescents who perceived themselves as having both strengths and weaknesses were more likely to seek negative feedback regarding a self-perceived weakness compared to a self-perceived strength. The authors found similar support for self-verification processes when they considered the entire sample regardless of perceived strengths and weaknesses; hierarchical linear modeling (HLM) examined the predictive power of ratings of self-perceived ability, certainty, and importance on feedback seeking for all participants and provided additional evidence of self-verification strivings in adolescence.